Microstructural diffusion MRI for differentiation of breast tumors and prediction of prognostic factors in breast cancer - Wang, Xiaoyan; Zhang, Yan; Cheng, Jingliang; Lin, Liangjie; Hu, Ying; Wang, Anfei; Zhang, Yong; Wang, Ruhua; Li, Ying; Zhang, Kun; Zhang, Wenhua (Frontiers in Oncology, 2025)
PurposeThis study aims to investigate the feasibility of cellular microstructural mapping by the diffusion MRI (IMPULSED, imaging microstructural parameters using limited spectrally edited diffusion) of breast tumors, and further to evaluate whether the MRI-derived microstructural features is associated with the prognostic factors in breast cancer.Materials and methodsThis prospective study collected 232 patients with suspected breast tumors from March to August 2023. The IMPULSED MRI scan included acquisitions of diffusion MRI using both pulsed (PGSE) and oscillating (OGSE) gradient spin echo with the oscillating frequencies up to 33 Hz. The OGSE and PGSE data were fitted by the IMPUSLED method using a two-compartment model to estimate mean cell diameter (dmean), intracellular fraction (fin), extracellular diffusivity (Dex), and cellularity index (fin/d) within breast tumor lesions. The apparent diffusion coefficients (ADCs) were calculated from the conventional diffusion weighted imaging, PGSE, and OGSE (17 Hz and 33 Hz) sequences (ADCDWI, ADCPGSE, ADC17Hz, and ADC33Hz). The independent samples test was used to compare the dmean, fin, Dex, cellularity index, and ADC values between benign and malignant breast tumors, and between breast cancer subgroups with different risk factors. The receiver operating characteristic (ROC) curve was used to access the diagnostic performance.Results213 patients were finally included and divided into malignant (n=130) and benign (n=83) groups according to the histopathological results. The dmean (15.74 ± 2.68 vs. 14.28 ± 4.65 μm, p<0.001), fin (0.346 ± 0.125 vs. 0.279 ± 0.212, p<0.001) and cellularity index (21.19 ± 39.54 vs. 19.38 ± 14.87 ×10-3 um-1, p<0.005) values of malignant lesions were significantly higher than those of benign lesions, and the Dex (2.119 ± 0.395 vs. 2.378 ± 0.332 um2/ms, p<0.001) and ADCDWI (0.877 ± 0.148 vs. 1.453 ± 0.356 um2/ms, p<0.001) of malignant lesions were significantly lower than those of benign lesions. For differentiation between benign and malignant breast lesions, ADCDWI showed the highest AUC of 0.951 with the sensitivity of 80.49% and specificity of 98.28%. The combination of dmean, fin, Dex, and cellularity for differentiation between benign and malignant breast lesions showed AUC of 0.787 (sensitivity = 70.73%, and specificity = 77.86%), and the combination of IMPULSED-derived parameters with ADCs by PGSE and OGSE further improve the AUC to 0.897 (sensitivity = 81.93%, and specificity = 81.54%). The fin values of HER-2(+) tumors were significantly lower than those of HER-2(-) tumors (0.313 ± 0.100 vs. 0.371 ± 0.137, p=0.015), and the ADCDWI, ADC17Hz and ADC33Hz values of HER-2(+) tumors were significantly higher than those of HER-2(-) tumors (ADCDWI: 0.929 ± 0.115 vs. 0.855 ± 0.197 um2/ms, p=0.023; ADC17Hz: 1.373 ± 0.306 vs. 1.242 ± 0.301 um2/s, p =0.025; ADC33Hz: 2.042 ± 0.545 vs. 1.811 ± 0.392 um2/s, p = 0.008). The fin (0.377 ± 0.136 vs. 0.300 ± 0.917, p=0.001) and cellularity index (27.22 ± 12.02 vs. 21.66 ± 7.76 ×10-3 um-1, p=0.007) values of PR(+) tumors were significantly higher than those of PR(-) tumor. The ADC17Hz values of PR(+) tumors were significantly lower than those of PR(-) tumors(1.227 ± 0.299 vs. 1.404 ± 0.294 um2/s, p =0.002).The ADC17Hz and Dex values of ER(+) tumors were significantly lower than those of ER(-) tumors (ADC17Hz: 1.258 ± 0.313 vs. 1.400 ± 0.273 um2/s, p = 0.029; Dex: 2.070 ± 0.405 vs. 2.281 ± 0.331 um2/ms, p=0.011). For differentiation between ER(+) and ER(-), the ADC17Hz and Dex showed AUCs of 0.643 (sensitivity = 76.67%, and specificity = 47.06%) and 0.646 (sensitivity = 80.0%, and specificity = 45.98%), and the combination of Dex and ADC17Hz showed AUCs of 0.663 (sensitivity =93.33%, specificity = 36.78%). For differentiation of PR(+) and PR(-), the ADC17Hz, fin, and cellularity index showed AUCs of 0.666 (sensitivity = 68.18%, and specificity = 61.97%), 0.697 (sensitivity = 77.27%, and specificity = 60.27%) and 0.661 (sensitivity = 68.18%, and specificity = 61.64%), respectively, and their combination showed AUCs of 0.729 (sensitivity =72.73%, specificity = 65.75%). For differentiation of HER-2(+) and HER-2(-), the ADCDWI, ADC17Hz, and ADC33Hz, and fin showed AUCs of 0.625 (sensitivity = 59.42%, specificity = 63.04%), 0.632 (sensitivity = 43.66%, and specificity = 84.78%), 0.664 (sensitivity = 47.95%, and specificity = 82.67%) and 0.650 (sensitivity = 77.46%, and specificity = 56.52%), respectively, and their combination showed AUCs of 0.693 (sensitivity = 69.57%, specificity = 64.79%) of HER-2(+) and HER-2(-).ConclusionThe IMPULSED method demonstrates promise for characterizing cellular microstructural features in breast tumors, which may be helpful for prognostic risk evaluation in breast cancer.